Análise exploratória de práticas de ESG do setor privado com potencial de fomento ao programa município VerdeAzul - Biasin, Vinícius Tramontina (Universidade Federal de São Carlos, 2025)
The accelerated growth of urban centers and the resulting socio-environmental impacts have intensified the debate on effective monitoring metrics that could contribute to the promotion of sustainable development. In this scenario, the Sustainable Development Goals (SDGs), proposed by the UN in 2015, guide public policies at various scales, influencing local initiatives such as the Programa Município VerdeAzul (PMVA), created by the Secretaria de Meio Ambiente, Infraestrutura e Logística do Estado de São Paulo (SEMIL). The PMVA proposes an evaluation structure based on technical guidelines that aim to stimulate municipal environmental management based on criteria such as governance, environmental education, solid waste, air quality, among others. However, for municipalities to perform well in the program, it is necessary to overcome challenges such as the scarcity of financial and technical resources. In this context, partnerships with the second sector emerge as strategic alternatives, promoting collaborative actions that align public and private interests. In this context, this work identifies, from the the Merco (Corporate Reputation Business Monitor) ESG (Environmental, Social and Governance) Responsibility Ranking, initiatives of leading companies in sustainability and analyzes how these actions can be adapted and replicated to strengthen the performance of municipalities in the PMVA guidelines. Based on the analysis of sustainability reports, practices with strong potential for local impact were identified, reinforcing the importance of public-private partnerships as an instrument to accelerate the green transition and achieve environmental and social goals in an integrated manner.
Exploratory analysis of private sector ESG practices with potential to promote the VerdeAzul municipal program
Keywords: Sustentabilidade; Governança; ODS; Relatórios; Desenvolvimento; Sustainability; Governance; SDGs; Reports; Development; ENGENHARIAS